The Effectiveness of Imagination in The Transformations of Functional Substitution of The Senses in Sufi Poetry - Hashiyar Zaki Hassan; Suha Salah Muhiyadin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
It is the imagination in the work of art that performs the process of monotheism, and the image is his tool and its means, through which he exercises his activity and effectiveness, and is directly responsible for the birth and creativity of the image, so the imagination works in the initial material of the experience (feeling), and destroys it to give it a new form, because imagination does not stop at the realistic and tangible limits of things and assets, but its activity and effectiveness go beyond all of this to further distances, It re-engages objects and assets and creates and produces new and unique relationships between dissonances and divergences, thus creating a kind of harmony, harmony and harmony between them, hence the subjectiveness of imagination, and becomes a fundamental effective tool that distinguishes each poet from others, and since the world of fiction is the link between sense and reason, the format of images is therefore adapted through the dialectic of combining the opposites in a visual, invisible, real, present and non-existent form. Imagination in general creates a new and innovative image of reality, it is a creative activity, which prompts the recipient to re-reflect on his reality through a poetic vision, deepening his sense and enriching it, and strengthening his consciousness, as the messaging of the senses opens the way to express things in the same poet that he can express only by them, which is meant to communicate with the senses the description of sensory perceptions in other sense perceptions, which is one element of the imagination manifested in poetry, Where the word increases luster and shine, and the meaning depth and influence, mixing one sense with another breaks the routine and increases the attention of the recipient, and expands the horizons of his idea, the poet depends on all his senses in the composition of his poetic image, and then formulates it with his creative abilities and cultural experiences, because sensory elements are the basis of the composition of the image of the poet and his ability to formulate his poetic vision in a pictorial form in which the truth blends imagination.